Simulation of ions interaction with biological environment using Geant4 - S. O. Liulchenko; M. О. Zhovner; O. M. Kalinkevich (Ядерна фізика та енергетика)
Computer model that makes it possible to study the interaction of ion beam with biological objects has been created. Contribution of secondary particles to the formation of the total radiation dose was investigated. The model contains all the necessary elements of formation of ion beam and we can interactively change the parameters of the model. For processing of simulation results additional program codes were created. Studies were carried out on the object which size and physicochemical properties are similar to biological cell in the human body.